Vortex measurement at bell-shaped pump inlet using particle image velocimetry - Muhammad Azhar Akbar Batcha; Tajul Ariffin Norizan; Zulkhairi Zainol Abidin; Zambri Harun; Wan Hanna Melini Wan Mohtar (Penerbit Universiti Kebangsaan Malaysia, 2018)
The vortex formed at the pump intake is known to be the main factor affecting the performance of a pump and it contributes directly to the increase of energy consumption. This study was aimed at obtaining an in-depth visualization and identifying the characteristics of the vortices generated by the installation of a bell-shaped suction inlet in a pump-induced flow using particle image velocimetry (PIV). A complementary metal-oxide semiconductor (CMOS) camera was used to capture images of the illuminated bubbles in a sump pump model. The PIV images were analysed using PIVlab, which provided representations of the 2-D plane velocities and vorticities around the inlet of the pump. The measurements were taken at four different planes that were coaxial with the bell circumference below the bell inlet. The results showed that the diameter of the vortex structure became smaller as it approached the bell inlet. Higher values of vorticity were observed within the vortex core, which conformed to the characteristics of a vortex formation. The velocity profiles exhibited the proportionality of the velocity against the radius of the vortex, which categorized this as a forced vortex. The findings from the study will be utilized by the Department of Irrigation and Drainage (DID) Malaysia to develop remedial measures for problems related to the formation of vortices in sump pumps.